Prevelance and pathogenicity of root lesion nematode, Pratylenchus spp. on banana (Musa paradisiaca L.) in Peninsular Malaysia - Paiko, Adamu Saidu (2016)
Root lesion nematode (Pratylenchus spp.) cause considerable damage to banana plant (Musa spp.) globally. Even though, it has been reported in Malaysia, it disease prevalence and severity of infection has not been attended to. The objective of the research therefore, was aimed at determining the disease prevalence of Pratylenchus spp. and the status of their damage on Musa spp. in Peninsular Malaysia. To study the prevalence and pathogenicity of root lesion nematode, Pratylenchus spp. on banana (Musa paradisiaca.) in Peninsular Malaysia, samples of soil and root were collected from banana fields nationwide in 2014. Of the 13 sampled banana fields, lesion nematodes were found in 10 fields (76% of the areas surveyed). Rating of root cortex occupied by reddish brown lesion was significant among all the states, with Johor having the highest disease severity of 36.3% followed by Selangor 20.7%, Perak 20.2% and Pahang 20.4 % respectively. The study found that all the sampled areas have exceeded threshold limit, which is 5%. Mean population density of fields having Pratylenchus spp. from 20 g roots and 200 g soil were significantly different, where population mean of Selangor, (root= 838 and soil= 897), (root= 18,050 and soil= 13,056) in Johor, (root= 2341 and soil= 461) Perak and (root= 11,315 and soil= 7,199) Pahang were recorded. Other plant-parasitic nematodes identified were Rotylenchulus spp., Meloidogyne spp., Helicotylenchus spp., Hoplolaimus spp. and Radophulus simili. Pathological reaction of P. coffeae against banana cultivar berangan (Musa paradisica) multiplications was observed after 12 weeks of growth. There were significant differences in vegetative growth within the various pathogens inoculation levels evaluated. Multiplication factors ranged between 1.6-4 in P. coffeae. Reduction in root length (-23.68 to -84.95), shoot length (-13.11 to -45.80), root weights (-21.30 to -99.85) and shoot weight (-9.30 to -61.62) lengths were recorded at (P≤ 0.05) level of probability. Banana cultivar berangan showed high level of susceptibility through the activity of polyphenol oxidase and peroxidase-induced resistance at all days after inoculation with P. coffeae compared to the control, except at week 12 where it declined or non-significant with the control. Our observations from this study, revealed that P. coffeae is among the most damaging plant-parasitic nematode species associated with banana in Peninsular Malaysia replacing R. similis, which is seldom reported or localized to a particular area and in low densities, followed by Meloidogyne spp. That it is common on banana cultivar berangan in this country, and that its geographical distribution is not restricted. Although the morphological study of the female populations of P. coffeae from Peninsular Malaysia gave some little variation in morphology from the reference sources, we resolved that these variations are within the range of the previously described morphological variations in P. coffeae populations from other parts of the world, thus, confirming that the isolates were P. coffeae. In general, the glass house pathogenicity trial of P. coffeae, suppresses vegetative growth of the banana cultivar berangan significantly. Root lesion indexes showed higher disease severity at all inoculum levels evaluated. It can be concluded that P. coffeae is widely distributed and caused significant damage to banana crop in Peninsular Malaysia.